X+(-5)=-11

Simple and best practice solution for X+(-5)=-11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for X+(-5)=-11 equation:


Simplifying
X + (-5) = -11
X + -5 = -11

Reorder the terms:
-5 + X = -11

Solving
-5 + X = -11

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '5' to each side of the equation.
-5 + 5 + X = -11 + 5

Combine like terms: -5 + 5 = 0
0 + X = -11 + 5
X = -11 + 5

Combine like terms: -11 + 5 = -6
X = -6

Simplifying
X = -6

See similar equations:

| 7p-9=6p-1 | | 4=-08n | | 2-2w+49=4+w+32 | | 3(x-5)=3x+1 | | h=-4t^2+3t+1 | | t/5-8=10 | | -4x-3y=-21 | | 2(x+4)=5x+44 | | 2v^2=35+9v | | 9v=v+16 | | 2*x^2=18 | | 8(4+x)=200 | | -5x-y=4 | | 4a=2a+40 | | -8n-35=3(1+2n)+4 | | 2r+62=5r+38 | | x^3-12x^2-13x=0 | | 3b+19=4b | | t//5-8=10 | | u+21=5u-47 | | 3-4(m-2)=-5m+13 | | (-6x-11)+(5x+12)= | | 6t+13=7t | | -4-x=14-0 | | 5y+12=y+20 | | v-34+v-43=v+5 | | 11x-6=-303 | | 5+4=2090 | | (b-7)+(3b+9)= | | 5/11m-1/2=2/3 | | -4-0=14-3y | | 8x+3=-0.2x+12.6 |

Equations solver categories